Asertivitas Mahasiswa Organisatoris Ditinjau dari Kecerdasan Emosional dan Jenis Kelamin - Dwilestari, Ni Made Ayu Krisna; Widiasavitri, Putu Nugrahaeni (Jurnal Psikologi Udayana; Vol 9 No 1 (2022)DO - 10.24843/JPU.2022.v09.i01.p02, 2022)
Assertiveness is the ability to express thoughts, feelings, needs, and desires with confidence that does not harm yourself or violate the rights of others. In college life, students do not just focus on academic activities but also non-academics, such as student organizations. When participating in organizations, students are faced with some situations that require assertiveness skills. Assertiveness can be influenced by two factors, including emotional intelligence and gender. This quantitative research aims to determine the role of emotional intelligence and gender on the assertiveness of Udayana University Medical Faculty students participating in student organizations. The subjects of this research were 120 students of Udayana University Medical Faculty students participating in student organizations. There are two measuring instruments used in this research, that are assertiveness scale and emotional intelligence scale. This research used analysis of covariance or ANOVA as data analysis technique. The results show the significance value on the corrected model is 0.000 (p <0,05). These results show that emotional intelligence and gender altogether contribute to the assertiveness of Udayana University Medical Faculty Students participating in student organizations.